ANALISIS KEAMANAN LAYANAN E-LEARNING TERHADAP SERANGAN DoS DAN IMPLEMENTASI MITIGASI PADA UNIVERSITAS BUDI LUHUR - Joko Christian Chandra (Jurnal Ticom: Technology of Information and Communication, 2022)
Budi Luhur University in Jakarta has Electronic Learning (E-Learning) services. This service is very crucial in carrying out teaching and learning activities, especially during the online learning period, so that any service failure in any form will have a major impact. The e-learning service in question is web-based with a client-server communication approach. Using a single server, e-learning web services are vulnerable to security attacks, especially Denial of Service (DoS) and Distributed Denial of Service (DDoS) types. DoS attacks are a form of attack that consumes existing server resources, so that services to valid users are interrupted or disconnected. Quantitative data for service vulnerability has not been measured and the implementation of mitigation measures is still low. Based on these circumstances, this study examines the related system components, using methods compiled from previous studies to measure server security levels, formulate mitigation plans, and implement the necessary mitigations. The result of this research is an increase in security against certain types of DoS and DDoS attacks, so that E-learning services have lower down time due to these attacks.